Cassava roots damaged by Migdolus fryanus produce poor quality starch - Guerreiro, Julio César; Azevedo, Ana Paula; Prado, Evandro Pereira [UNESP]; Pietrowski, Vanda; Ringenberg, Rudiney; Moritz, Cristiane Mengue Feniman; Giotto, Thais Carneiro; Pascutti, Thaíse Milena; Ferreira-Filho, Pedro José (Revista de Agricultura Neotropical, 2022)
The aim of this study was to evaluate the quality of starch produced by plants that suffer damage caused by M. fryanus, analyzed by colorimetric and morphological indices. Colorimetric data were composed of luminosity indices, a and b chroma coordinates and darkening index. For morphological data, the perimeter and area of starch granules extracted from cassava roots were analyzed. The variables were summarized in a principal component analysis and the axes scores retained for interpretation were correlated with the damage caused by the M. fryanus. From these analyses and observing the main effects, linear regression models for the variables were determined, according to the level of damage caused by the pest. The damage caused by M. fryanus in the roots strongly influenced the indices related to starch colorimetry, hence, under conditions of greater damage, the tendency of the chroma coordinates to vary toward red and yellow was observed and a decrease in starch luminosity occurred, inversely proportional to the increase in darkening. Similar to what was observed in the colorimetric data, a drop in the size of starch granules was noted in the roots, which suffered greater damage from the pest.
Raízes de mandioca danificadas por Migdolus fryanus produzem amido de baixa qualidade
Keywords: Pests; Processing industry; Soil pests; Tuberous roots